Implikasi Penerapan Undang-Undang Koperasi Pada Meningkatkan Prestasi KP3A Kota Padang Sebagai Koperasi Terbaik Di Kota Padang - Sri Agustini (Journal of Global Legal Review, 2024)
Cooperatives are a form of economic organization owned and operated by its members to fulfill common needs and aspirations. The main principle of cooperatives is cooperation and togetherness among its members. The purpose of this study is to examine the impact of the implementation of Cooperative Law Number 25 of 2020 concerning Cooperatives, on the performance of KP3A Kota Padang, which has been recognized as the best cooperative in Kota Padang. This research aims to provide an in-depth analysis of how specific legislative measures have influenced the operational success and overall achievements of KP3A Kota Padang. This study employs a qualitative approach, utilizing interviews, observations, and document analysis to gather comprehensive data on the cooperative's practices and outcomes. The research findings reveal that the enforcement of cooperative laws has significantly contributed to the improvement of management efficiency, member satisfaction, and financial performance of KP3A. The study concludes that the strategic application of cooperative laws is crucial in driving the success and sustainability of cooperatives, as evidenced by the outstanding performance of KP3A Kota Padang.